Evaluation of different hormone inducers on the reproduction of Prochilodus brevis males - Carla Tatiana Nascimento Sousa Vieira; Yara Silvino Sales; Jessica Sales Lobato; Marcos Luiz da Silva Apoliano; Yasmim Maia Ferreira; Silvio Alencar Cândido-Sobrinho; Vanessa Alves Pereira; Carminda Sandra Brito Salmito-Vanderley (Revista Ciência Agronômica, 2023)
ABSTRACT The use of carp pituitary extract (CPE) in fish reproduction may have drawbacks, whereas analogues of mammalian (aGnRHm) or salmon (aGnRHs) gonadotropins containing dopamine inhibitor (DI) may offer greater advantages. The objective of this study was to evaluate the effect of different hormone inducers on the reproduction of Prochilodus brevis males. A total of 44 specimens of P. brevis were divided into six groups, namely, CPE 4.0 mg; saline solution 1.0 mL; aGnRHm + DI 0.3 mg and 0.5 mg; and aGnRHs + DI 0.25 mL and 0.35 mL kg-1 of live weight. The number of ejaculates, seminal volume, curvilinear velocity (VCL), straight-line velocity (VSL), average path velocity (VAP), sperm morphology and concentration, and membrane and DNA integrity were determined. Sample normality was examined using the Shapiro-Wilk test, and homogeneity using the Levene test. Analysis of variance (ANOVA) was conducted, followed by Tukey's test to compare means, with statistical significance set at p < 0.05. Notably, all fish induced with CPE 4.0 and aGnRHm + DI demonstrated ejaculation, yielding a greater seminal volume. Sperm concentration under aGnRHs + DI 0.35 exceeded that with aGnRHm + DI 0.3 and CPE 4.0. Regarding velocity, aGnRHm + DI 0.3 outperformed aGnRHs + DI 0.35 in VCL, while aGnRHm + DI 0.3 and 0.5 and aGnRHs + DI 0.25 led to higher VSL than aGnRHs 0.35. Additionally, VAP was elevated under aGnRHm + DI 0.3 and CPE, in contrast to aGnRHs + DI 0.35. Improved sperm morphology was observed with aGnRHm + DI 0.5 and aGnRHs + DI 0.25 compared to aGnRHm + DI 0.3. The remaining parameters did not differ significantly.